An Analysis Women’s Language Feature Used by Erin Gruwell in Freedom Writers Movie - Khoirummuthmainnah, Khoirummuthmainnah; Kholid, Muhammad Ridho; Hidayat, Agus (Raden Intan State Islamic University of Lampung, Indonesia, 2024)
All Gender is one of the factors that can influence the way a people used a language. Gender is a characteristic of men and women that influences their social environments. people have various styles of language when communicating with people with different social classes in society. Therefore, the researcher chose to analyze the women’s language used by Erin, an English teacher who tried to change his students' point of view in the movie entitled The Freedom Writers. The research method used in this study is a qualitative research design it investigates the utterances of women’s language feature used by Erin as the main character in Freedom writers movie by using human as the instrument. In content analysis, the researcher watch and read to understand the movie, listing the utterances by Erin as the main character in Freedom Writers movie. Then the researcher analyzed by identifying the data which were categorized as type of women’s language feature. Analyzing the data based on Lakoff’s theory: lexical hedges or fillers, tag questions, rising intonation on declaratives, ‘empty’ adjectives, precise color terms, intensifiers, ‘hypercorrect’ grammar, ‘superpolite’ forms, avoidance of strong swear words, and emphatic stress. From the data analysis, the result of this study showed that: (1) there are eight type of women’s language feature used by Erin as the main character in freedom writers movie consisted lexical hedges or fillers, tag questions, rising intonation on declaratives, ‘empty’ adjectives, intensifiers, ‘hypercorrect’ grammar, ‘superpolite’ forms and avoidance of strong swear words. (2) the dominant type used by Erin in freedom writer movie is “hypercorrect” Grammar.